2010
DOI: 10.1249/mss.0b013e3181c524b7
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Compensatory Adjustments to Exercise Training in Overweight Women

Abstract: Purpose: To examine extent to which changes in non-exercise physical activity contribute to individual differences in body fat loss induced by exercise programs. Results: Over the 8-week exercise program net ExEE was 30.2 ± 12.6 MJ and based on this, body fat loss was predicted to be 0.8 ± 0.2 kg. For the group as a whole, change in body fat (-0.0 ± 0.2 kg) was not significant but individual body fat changes ranged from -3.2 kg to +2.6 kg. Eleven participants achieved equal or more than the predicted body fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 30 publications
5
88
1
1
Order By: Relevance
“…Residuals between observed and predicted REE were calculated to estimate adaptations in REE that could not be attributed to changes in FFM (39).…”
Section: Methodsmentioning
confidence: 99%
“…Residuals between observed and predicted REE were calculated to estimate adaptations in REE that could not be attributed to changes in FFM (39).…”
Section: Methodsmentioning
confidence: 99%
“…There were no differences in RMR between groups. While EI did increase significantly from baseline in both groups, there were no significant between group differences in the number of kcals consumed or macronutrient composition (Manthou et al, 2010).…”
Section: Mechanisms Of Compensationmentioning
confidence: 61%
“…Stubbs et al, 2002;Woo & Pi-Sunyer, 1985). However, Manthou et al found that compensators, and not non-compensators, had a significant decrease in NEAT during an eight week study, and that this decrease in NEAT was a significant predictor of fat mass changes during the exercise intervention (Manthou et al, 2010). Additionally, Church et al found that exercising and control groups had no significant step count differences at baseline, but that the control group had a significantly higher step count as compared to all exercise groups during the first four weeks of an exercise intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations